Influence of the amount of calcium sulfate on physical/mineralogical properties and carbonation resistance of CSA-based cements. (January 2022) - Bertola, F.; Gastaldi, D.; Irico, S.; Paul, G.; Canonico, F.
Abstract: Binary and ternary binders, Calcium SulfoAluminate (CSA) clinker plus anhydrite (A) and blends of Portland cement, CSA clinker, and A, respectively, are examined in order to understand the effect of the A/CSA clinker ratio (A/CSA) on hydration process, physico-mechanical properties and durability against carbonation. The study revealed that: (i) in binary systems the increase of the A/CSA has a positive influence on the physical performance, but worsens the resistance against carbonation (ii) in ternary systems a non-linear behavior related to the physical aspects is observed, being the system with the intermediate A/CSA the best performer in terms of dimensional stability and carbonation resistance. The effect of carbonation on the hydrate phase assemblage was studied through a multi-technique approach and results were supported by thermodynamic models, indicating that the optimal dosage of sulfates is strictly dependent on the carbonation exposure and the ternary systems are more durable than the binary ones.